2014
DOI: 10.1016/j.biopsych.2013.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Selective, Retrieval-Independent Disruption of Methamphetamine-Associated Memory by Actin Depolymerization

Abstract: Background Memories associated with drugs of abuse, such as methamphetamine (METH), increase relapse vulnerability to substance use disorder. There is a growing consensus that memory is supported by structural and functional plasticity driven by F-actin polymerization in postsynaptic dendritic spines at excitatory synapses. However, the mechanisms responsible for the long-term maintenance of memories, after consolidation has occurred, are largely unknown. Methods Conditioned place preference (N=112) and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 79 publications
11
97
0
Order By: Relevance
“…METH impact on actin filaments was observed in previous studies that reported either actin depolymerization, altered cell shape, local accumulation of condensed actin, or disruption of the F-actin parallel strands, leading to compromised TJ function [14,26,45]. In our study, METH exposure led to a dramatic loss of F-actin integrity concomitant with claudin-5 redistribution and decreased expression.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…METH impact on actin filaments was observed in previous studies that reported either actin depolymerization, altered cell shape, local accumulation of condensed actin, or disruption of the F-actin parallel strands, leading to compromised TJ function [14,26,45]. In our study, METH exposure led to a dramatic loss of F-actin integrity concomitant with claudin-5 redistribution and decreased expression.…”
Section: Discussionsupporting
confidence: 71%
“…Importantly, METH-induced BBB increased permeability was associated with reduction and/or redistribution of TJ proteins [10,13]. There is also evidence that it can interfere with actin structure and arrangement, which also may lead to compromised TJ function [14,26]. Although the molecular mechanisms underlying BBB disruption under METH exposure are not fully characterized, the activation of matrix metalloproteinases (MMPs), commonly involved in remodeling and degradation of the neurovascular matrix components and therefore associated with BBB leakiness, has been reported [4,6,9,27].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, latrunculin microinjection into the NAcore potentiated cocaine-induced reinstatement, indicating that the increase in F-actin after cocaine withdrawal may be compensatory relative to drug-seeking behavior (Toda et al, 2006(Toda et al, , 2010. In a similar line of research, others found that inhibition of actin cycling in the amygdala selectively disrupted methamphetamine-associated memory in methamphetamine CPP and contextual renewal of methamphetamine seeking (Young et al, 2014).…”
Section: Functional Relevance Of Spine Dynamicsmentioning
confidence: 92%
“…Animal modeling of BPD behavior (to determine the response to lithiumresponse pathway manipulation) was as described previously (37)(38)(39) …”
mentioning
confidence: 99%